2021
DOI: 10.15414/jmbfs.2021.10.4.631-635
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND CHARACTERIZATION OF BIOACTIVE COMPOUNDS IN MEDICINAL PLANT Centella asiatica AND STUDY THE EFFECTS ON FUNGAL ACTIVITIES

Abstract: Preparation of plant crude methanol extract Centella asiatica were purchased from the local retail market. All plant materials washed thoroughly under running tap water and air dried at room temperature for two days and ground into a fine powder. The air-dried and powdered plant material are extracted with 400 ml of 95.5% methanol, kept in the room temperature for 72 h with periodic stirring. Thereafter the extract was filtered by Medicinal plants are sources of important therapeutic aids for alleviating human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Therefore, the presence of rutin (flavonoid) and oleic acid in the extract promotes the production of antioxidants [22]. In this study, hexadecenoic acid was the second-highest compound found in C. asiatica, in which Bhuyar et al [17] also reported the presence of hexadecanoic acid (99 %) in C. asiatica extract, and the compound is known to be antimicrobial. Many valuable compounds extracted from C. asiatica by SFME showed that this method is a promising green method with faster extraction.…”
Section: Phytochemical Analysis Of Centella Asiatica Extractmentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore, the presence of rutin (flavonoid) and oleic acid in the extract promotes the production of antioxidants [22]. In this study, hexadecenoic acid was the second-highest compound found in C. asiatica, in which Bhuyar et al [17] also reported the presence of hexadecanoic acid (99 %) in C. asiatica extract, and the compound is known to be antimicrobial. Many valuable compounds extracted from C. asiatica by SFME showed that this method is a promising green method with faster extraction.…”
Section: Phytochemical Analysis Of Centella Asiatica Extractmentioning
confidence: 51%
“…The presence of cyclohexane in C. asiatica is expected since most of the polyacetylene compounds were found in the Apiaceae family. A study by Bhuyar et al [17] found hexadecanoic acid as a major compound in C. asiatica extract. The extract was high in fatty acids, which is in agreement with a study by Ogunka-Nnoka [18], who detected 78.48 % saturated and 21.53 % unsaturated.…”
Section: Phytochemical Analysis Of Centella Asiatica Extractmentioning
confidence: 99%
“…More than two-thirds of the drugs currently used in cancer treatments come directly from natural products (Gurnani et al, 2014). Much recent researches have great interest in screening of medicinal plants for new therapeutics (Bhuyar et al 2021). Because of their efficacy, safety, and availability (Naczk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their efficacy, safety, and availability (Naczk et al, 2006). The secondary metabolites existed in plants are manly used as active principals of many drags (Bhuyar et al 2021). Ammodaucus leucotrichus Coss belongs to the apiaceae family and Ammodaucus genus.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that green algae often act as a dominant group of plants in freshwater plankton. Besides, there is a variety of different biologically active substances (Hasbi et al, 2021;Bhuyar et al, 2020). However, despite this fact, the researches on the interactions of various species of green algae with pathogenic leptospira are extremely insufficient.…”
Section: Introductionmentioning
confidence: 99%